Building multi-professional UK partnerships and networks to improve access to palliative care for people experiencing homelessness - Briony Hudson; Jodie Crooks; Caroline Shulman; Kate Flemming (Public Health Research)
Background People experiencing homelessness have high rates of multi-morbidity and age-related conditions at a young age. Despite having high support needs, they have disparately low access to palliative care services and often die at a young age. To facilitate access to support for this group towards the end of life, a multi-professional approach should be taken. Over recent years, clinical and research activities have begun to address this issue. However, until now, there has been no centralised United Kingdom-based group to facilitate collaboration and shared learning. Aim To build multi-professional partnerships across the United Kingdom to promote shared learning and a multidisciplinary approach to supporting people experiencing homelessness who may be approaching the end of their lives. Method This project had three workstreams: (1) development of a Palliative Care and Homelessness Extensions of Community Healthcare Outcomes network; (2) a rapid review around involving people with experience of multiple exclusion in palliative and end-of-life care research; and (3) a qualitative study to identify recommendations for involving people with lived experience of homelessness in future palliative and end-of-life care research. Results: Workstream 1 A National Palliative Care and Homelessness Extensions of Community Healthcare Outcomes (ECHO) network was successfully established in the UK, with 10 sessions running over 12 months. A total of 268 people registered to the network, with an average of 52 participants per session. Evaluation of the network illustrated positive experiences and appetite for continuation of the network. The majority of attendees surveyed (78%) agreed that the network had increased their awareness of complexities and challenges faced by people experiencing homelessness and 85% of respondents reported better connections with others who are interested in or are working in this field. Workstream 2 A rapid review was conducted to summarise existing evidence and reflections on co-producing palliative care research with inclusion health groups, including people with lived experience of homelessness. Given the scarcity of existing research within this area, the review provided a starting point from which to explore the successes and challenges of co-research in this field. The review advocates for greater guidance around the involvement of people with lived experience of homelessness in palliative and end-of-life care research. Workstream 3 Professionals with experience of involving people experiencing homelessness in their work were interviewed (n = 16), and focus groups were held with people with lived experience of homelessness (n = 11). Recommendations were co-developed to support researchers to involve people with lived experience of homelessness in their palliative and end-of-life care research – the TIFFIN recommendations. Conclusion This project has highlighted the appetite for collaboration and shared learning among professional groups around supporting people experiencing homelessness who have advanced ill health. The TIFFIN recommendations, developed through this grant promote, trauma-informed, meaningful involvement of people with lived experience of homelessness in palliative and end-of-life care research. Due to the success of the network, a second round of sessions ran from November 2023 to November 2024, with a third round of the network planned for Spring 2025. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme as award number NIHR135250. Plain language summary People experiencing homelessness often have poor health and die at a young age, without support they need. Different professional groups must work together to ensure people get support that is right for them. Until now, there has been no central place for professionals to share ideas and collaborate. This project aimed to build connections between different professional groups who support people experiencing homelessness who are very unwell and may benefit from palliative and end-of-life care. There were three main parts: Developing a National Palliative Care and Homelessness Network Reviewing previous research about involving people with lived experience of homelessness in research. Co-developing recommendations for involving people with lived experience of homelessness in palliative and end-of-life care research. What did we do? We established an online National Palliative Care and Homelessness Network which met 10 times over a year, and continued beyond the duration of this project. Attendees reported feeling more confident, less isolated and using what they learned in their work. We also completed a rapid review which found very little research about how to involve people with lived experience of homeless in palliative care research. To fill this gap, we interviewed people with lived experience of homelessness who had been involved in research, and also researchers. Together, we identified recommendations for involving people with lived experience of homelessness in palliative and end-of-life care research. These are the TIFFIN recommendations, which include: Transparency. Importance of engagement and rapport. Facilitating equitable involvement via person-centred approach. Financial recognition of people’s involvement. Involvement and growth: a trauma-informed approach. Navigating institutional resistance and attitudes. The TIFFIN recommendations will be shared and used in our future research. We will maintain the national network to share best practice and facilitate connections with the aim of improving care and support for people experiencing homelessness who are very unwell.